Flame-Retarding and Mechanical Properties of Flexible Polyvinyl Chloride with Surface-Treated Lamellar Magnesium Hydroxide. Issue 2 (1st February 2016) - Liu, Xiaowei; Wu, Weihong; Qu, Hongqiang; Sun, Jianhong; Xu, Jianzhong
Abstract: The effects of hydrophobic magnesium hydroxide (Mg(OH)2 ) particles, prepared by a surface modification method with oleic acid, on the flame-retarding and mechanical properties of polyvinyl chloride (PVC) were investigated. Comparison between the use of modified and unmodified Mg(OH)2 in the preparation of PVC composites showed that the former could provide excellent optical and flame-retarding properties. The dispersion of the modified Mg(OH)2 particles in the PVC matrix was investigated through scanning electron microscopy. Compared with a composite containing unmodified Mg(OH)2, the rheological and impact strength properties of that containing the modified Mg(OH)2 filler were found to be significantly improved. These improvements were mostly attributed to the better dispersion of the modified Mg(OH)2 particles and the strong adhesion between the filler and matrix.